Sizing and finishing of non-circular internal bores using elasto-abrasives. (2015) - Sooraj, V.S.; Radhakrishnan, V.
Non-circular bores, typically cut with wire electric discharge machining, find extensive applications in industrial use. However sizing and fine-finishing of such internal surfaces, without altering its basic form, is a challenging task. Elasto-abrasive finishing is a recently introduced methodology, employing abrasive embedded elastomeric beads as the finishing medium. This paper discusses the application of elasto-abrasives in the form of meso-scale balls for progressive sizing and finishing of non-circular bores. Two types of elasto-abrasive balls with different elastomeric characteristics are introduced in this research, one for sizing cycle followed by the second for finishing. Processing of oval bores cut in hardened steel specimens, using Type II balls, yielded an average size variation of 10 µm in its radial dimensions without affecting the oval shape. The progressive processing of these specimens using Type I balls resulted in an average roughness of 0.03 µm, significantly reduced from its initial value of 0.2 µm.